2019
DOI: 10.1089/aut.2018.0035
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Autistic Advantage from the Accounts of Adults Diagnosed with Autism: A Qualitative Study

Abstract: Background: Autism has been associated with specific cognitive strengths. Strengths and weaknesses have traditionally been conceptualized as dichotomous. Methods: We conducted 28 semi-structured interviews with autistic adults. Maximum variation sampling was used to ensure diversity in relation to support needs. We asked which personal traits adults attributed to their autism, and how these have helped in the workplace, in relationships, and beyond. Data were collected in two stages. Responses were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 45 publications
7
101
1
1
Order By: Relevance
“…Interestingly, while there are sometimes clashes between perceptions and priorities of autistic self-advocates and parents (e.g. Opar, 2019), our analysis found that parents of autistic youth had similar perceptions of autistic strengths as the autistic adults interviewed by Russell et al (2019). Specifically, both groups identified memory, tenaciousness, and creativity as strengths, while also expressing that traits act as both strengths and challenges.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, while there are sometimes clashes between perceptions and priorities of autistic self-advocates and parents (e.g. Opar, 2019), our analysis found that parents of autistic youth had similar perceptions of autistic strengths as the autistic adults interviewed by Russell et al (2019). Specifically, both groups identified memory, tenaciousness, and creativity as strengths, while also expressing that traits act as both strengths and challenges.…”
Section: Discussionmentioning
confidence: 59%
“…For example, preferences for structure may present as behavioral inflexibility, detail orientation may present as socially inappropriate preoccupations or perseveration, and other differences in learning and communication may present as social deficits and restricted/repetitive behaviors (American Psychiatric Association, 2013). However, several of these characteristics are also seen as strengths and may place autistic 1 individuals at an advantage (Mottron et al, 2013; Russell et al, 2019). Autism strengths identified in research include pattern detection, ability to direct attention, memory, visuospatial skills, attention to detail, pitch discrimination, and creativity (de Schipper et al, 2016; Happe & Frith, 2009; Mahdi et al, 2018; Meilleur et al, 2015).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…4,44,45 Some studies have reported negative experiences associated with autism including feeling the need to camouflage or mask traits to be perceived as normal by society, social groups, and employers, 5,46 whereas others describe strengths associated with autism such as strong memories, advanced knowledge, and systematic thinking. 47 These studies have provided a glimpse into the lived experiences of autistic people. However, specific emotions associated with these experiences and the degree to which these experiences are shared with autistic people who do not communicate through the language-based methodologies used in these studies remain unclear.…”
Section: Visual Scale Of Emotions (Aape)mentioning
confidence: 99%
“…In short, we largely agree with psychiatry as to what autism is (a difference of neurology) and feel that scientific research should play a key role in defining the diagnosis. Nonetheless, we believe that identification of autism should transition to a non-pathological system that allows inclusion of evidence-based neutral differences and strengths, recognizing that autistic traits can be strengths, challenges, or neutral depending on context (and are often deeply valued by autistic people ourselves; Russell et al [41]). And while we agree with psychiatry that autism emerges from neurological differences, we disagree with many assessments of how autistic people should be treated-and wish to call attention to the social, legal, and political context in which research and diagnosis take place.…”
Section: Allow For Near-term Further Revisions: As New Informationmentioning
confidence: 99%